Stigma towards schizophrenia in Cyprus: Does studying a mental health related programme make a difference? - Nikolaou, E.; Petkari, Eleni (SAGE Publications Ltd, 2022)
Background and aims: Students from mental health related programmes may display stigmatising attitudes towards people of schizophrenia, however there are no data available on this population in Cyprus. The purpose of the present study was (a) to examine the levels of contact and stigma towards schizophrenia in Cypriot students of programmes related to mental health and students of other programmes and (b) to examine whether the successful recognition of a person with schizophrenia through a vignette and the estimation of severity levels was related to stigmatising attitudes. Methods: The participants were undergraduate students purposively selected across Cypriot universities (N = 152). A vignette depicting a person with schizophrenia, followed by the OMI to examine stigma and the BAE to examine contact with mental illness were used to collect the data. Results: The results showed that studying a mental health related programme and being a man was associated with more positive views related to social integration. No further stigma dimensions were predicted by the included variables. Similarly, level of contact and being able to identify the mental condition and estimate its severity was not related to stigma. Conclusion: The results emphasise the need to develop educational interventions to tackle stigma across students independently of their study programme and enhance mental health related programmes with opportunities for structured contact with patients with mental illness. © The Author(s) 2021.
Keywords: level of contact; mental health stigma; mental illness vignette; Schizophrenia; university students; Scopus; JCR